Environmental Source of Arsenic Exposure - Jin-Yong Chung; Seung-Do Yu; Young-Seoub Hong (Korean Society for Preventive Medicine, 2014)
Arsenic is a ubiquitous, naturally occurring metalloid that may be a significant risk factor for cancer after exposure to contaminated drinking water, cigarettes, foods, industry, occupational environment, and air. Among the various routes of arsenic exposure, drinking water is the largest source of arsenic poisoning worldwide. Arsenic exposure from ingested foods usually comes from food crops grown in arsenic-contaminated soil and/or irrigated with arsenic-contaminated water. According to a recent World Health Organization report, arsenic from contaminated water can be quickly and easily absorbed and depending on its metabolic form, may adversely affect human health. Recently, the US Food and Drug Administration regulations for metals found in cosmetics to protect consumers against contaminations deemed deleterious to health; some cosmetics were found to contain a variety of chemicals including heavy metals, which are sometimes used as preservatives. Moreover, developing countries tend to have a growing number of industrial factories that unfortunately, harm the environment, especially in cities where industrial and vehicle emissions, as well as household activities, cause serious air pollution. Air is also an important source of arsenic exposure in areas with industrial activity. The presence of arsenic in airborne particulate matter is considered a risk for certain diseases. Taken together, various potential pathways of arsenic exposure seem to affect humans adversely, and future efforts to reduce arsenic exposure caused by environmental factors should be made.